3(2x+3)=4x-15

Simple and best practice solution for 3(2x+3)=4x-15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x+3)=4x-15 equation:


Simplifying
3(2x + 3) = 4x + -15

Reorder the terms:
3(3 + 2x) = 4x + -15
(3 * 3 + 2x * 3) = 4x + -15
(9 + 6x) = 4x + -15

Reorder the terms:
9 + 6x = -15 + 4x

Solving
9 + 6x = -15 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
9 + 6x + -4x = -15 + 4x + -4x

Combine like terms: 6x + -4x = 2x
9 + 2x = -15 + 4x + -4x

Combine like terms: 4x + -4x = 0
9 + 2x = -15 + 0
9 + 2x = -15

Add '-9' to each side of the equation.
9 + -9 + 2x = -15 + -9

Combine like terms: 9 + -9 = 0
0 + 2x = -15 + -9
2x = -15 + -9

Combine like terms: -15 + -9 = -24
2x = -24

Divide each side by '2'.
x = -12

Simplifying
x = -12

See similar equations:

| (x^2-y^2)dy/dx=xy | | 6+6r-5=8r+21-6r | | X-(1-x)=2 | | -2x^2+20x-47=0 | | 5(6-7)=10 | | X+3x+2=5x+6 | | -2x^2+20x-36=0 | | -2x^2+20x-39=0 | | 2(x+5)-x=x+10 | | 4x-3=2x-1/3 | | 45=9x+9 | | (Y)+y=2 | | -10x-17=167 | | 3*x+20=5*x-4 | | 4a^5-500a^2=0 | | 68hm=km | | r^2+12r-189=0 | | 9w+1+3(w+2)= | | 8x-14=x^2+x-2 | | 3-(4x-3)=1 | | -45+m=24 | | 6n-24=9-3n-3 | | K^2+8=56 | | p(2+5p)= | | 3/2=x/11 | | 2x-35(4+5)=40 | | 2lnx-1= | | (4x-52)+(x+32)+(.5x+46)= | | x-5=5+x | | 2z+12=3-z | | 3x+5+2x-1=3x+17 | | 6a-8=3a+7 |

Equations solver categories